Assessing the salt tolerance of Spirulina platensis freshwater strains and examining cheap culture media for cultivation of the potential strain - Tam, Luu Thi; Thom, Le Thi; Ha, Nguyen Cam; Hien, Hoang Thi Minh; Thu, Ngo Thi Hoai; Hong, Dang Diem (Vietnam Journal of Biotechnology, 2021)
Spirulina cyanobacteria have been widely cultivated to exploit products such as crude protein, vitamins, phycocyanin pigment... with high nutritional and pharmacological values. However, the commercialization of these products is still a challenging issue due to high biomass cost, which is mainly caused by expensive nutrients in the culture medium. In this study, from 11 freshwater S. platensis strains, by culture screening, we found 7 strains being capable of profitable growth on inexpensive seawater with salinity ranging from 5 - 30‰, and selected ST strain as the potential strain for further study. Natural seawater must be pretreated to remove ions that easily cause precipitation of nutrients in the culture medium such as Mg2+, Ca2+, SO42-… before using. The ST strain showed the best growth in the natural seawater medium with 30‰ salinity containing 3 g/L NaNO3, 0.5 g/L K2HPO4, 0.05 g/L FeSO4. This strain reached the highest biomass yield at 0.487 g/L and the specific growth rate (µ) of 0.12 x day-1; protein and phycocyanin contents reached 48.6% and 127 mg/g of dry biomass, respectively. There was no difference in the mentioned above values with biological statistical significance between this medium and SOT medium in distilled water. The ST strain biomass was qualified to be used for the production of functional foods. Results of this study provided scientific basis for the use of marine and brackish waters to produce biomass of this highly economic cyanobacterium.